Kloning cDNA lengkap penyandi ACCase subunit biotin carboxylase dari mesokarp kelapa sawit (Elaeis guineensis Jacq.) Cloning of full length cDNA encoding ACCase subunit biotin carboxylase from mesocarp of oil palm (Elaeis guineensis Jacq.) - Asmini BUDIANI; Antonius SUWANTO; Hajrial ASWIDINNOO; Djoko SANTOSO; Basil J NIKOLAU (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2013)
AbstractAcetyl-CoA Carboxylase (ACCase) is considered to beone of the key enzymes in palm oil biosynthesis. Availabilityof genes encoding this enzyme would give some advantagesin the molecular breeding of oil palm. Over expression ofthe genes in the oil palm mesocarp might increase the oilproduction in this tissue. On the other hand, downregulating of ACCase could divert the central metaboliteAcetyl-CoA to other product such as PHB (Polyhydroxy-butyrate), one of the known biodegradable plastic. Thispaper reported the work of cloning of the full length codingsequence of biotin carboxylase (BC), one subunit of theACCase. Based on the DNA sequence of the BC conservedregion that had cloned previously, primers pairs weredesigned to amplify 5’- and 3’- cDNA ends of BC usingRACE-PCR. The RACE products of 5’- and 3’- cDNA endsof BC were cloned into E.coli, and the DNAs weresequenced and analysed. The full cDNA of BC was obtainedby reisolation of the cloned 5’- and 3’- cDNA ends followedby digestion using KpnI, ligation into pGEM-T vector andcloning into E.coli. Colony PCR was carried out to confirmthat the target gene has been cloned. The recombinantplasmid containing full cDNA of BC was then isolated forDNA sequencing. The results showed that the 5’-BC (1367bp), 3’- BC (1032 bp), and the full length cDNA encodingBC (2182 bp) had been successfully cloned, and the DNAsequence had been confirmed as gene encoding ACCasesubunit biotin carboxylase.AbstrakAcetyl-CoA Carboxylase (ACCase) merupakan salahsatu enzim kunci dalam biosintesis minyak sawit. Keter-sediaan gen penyandi enzim ini sangat berguna dalampemuliaan kelapa sawit secara molekuler. Over-ekspresi genpenyandi ACCase pada mesokarp dapat meningkatkan pro-duksi minyak pada jaringan tersebut. Sebaliknya ekspresiACCase dapat ditekan melalui mekanisme down regulation sehingga metabolit central Acetyl-CoA dapat diarahkanuntuk menghasilkan produk lain seperti PHB (polyhydro-xybutyrate), salah satu jenis biodegradable plastik yangtelah banyak dikenal. Penelitian ini bertujuan untukmengklon cDNA lengkap penyandi ACCase subunit biotincarboxylase (BC) dari mesokarp kelapa sawit. Berdasarkansekuen DNA daerah konservatif BC yang telah diklon darimesokarp kelapa sawit pada penelitian sebelumnya, duapasang primer dirancang untuk mengamplifikasi daerahujung 5’- dan 3’- cDNA BC dengan RACE-PCR. Produk5’-RACE dan 3’-RACE diklon dan disekuen. cDNAlengkap penyandi BC diperoleh dengan jalan mengisolasikembali fragmen 5’- dan 3’- cDNA terklon, dilanjutkandengan digesti menggunakan enzim restriksi KpnI, ligasikedua fragmen ke vektor kloning pGEM-T, dan introduksike dalam E. coli. Setelah dilakukan PCR koloni untukmenguji keberhasilan kloning, plasmid rekombinan yangmengandung cDNA lengkap dari BC diisolasi untuk analisissekuen DNA. Dari penelitian ini fragmen cDNA 5’-BC(1367 pb) dan 3’- BC (1032 pb), serta cDNA lengkappenyandi BC berukuran 2182 pb telah diperoleh dan diklondalam E. coli. Analisis sekuen DNA mengkonfirmasi bahwacDNA terklon adalah benar gen penyandi ACCase subunitbiotin carboxylase.